Filosofia e desrazão : poder, resistência e estética na história da loucura de Michel Foucault - Testa, Federico (2012)
This thesis presents a possibility of reading Michel Foucault s Madness and civilization, reintegrating the first preface of the book and its problematic. The author interrogates Madness and civilization about a possible philosophy of experience and aesthetics, not made explicit by Foucault in his book. In the vicinity of the project of interrogating otherness, limits, transgression, and proscription, one of the fundamental questions of the book is seen as the one about culture and history. It's the question about its conditions of possibility, and about what remains for them as unthough or forgotten, and the fundamental structure of exclusion and segregation that constitutes them. It was based on the notion of archeology of silence that the dissertation poses the question about what was silenced (madness itself), and, secondly, about the gestures, actions and processes that reduced this subject to silence, that is, the history of the procedures of correctional power that are constituted in relation to the mad and the institutions that host them. It is as an archeology of the processes of capture and confinement of the insane - that deprive them of their language - that archeology can approach the conditions of possibility of the establishment of mental illness as an object of knowledge and therapy, and of mental medicine as a scientific knowledge. This idea of silence led, finally, to a discussion about the main modes of action of power in the history of madness, as well as an outline of precarious forms of resistance linked to transgressions of prohibitions of language. The task sketched on this thesis was to connect Madness and civilization to Foucault's reflection on art, literature and language, asking about an aesthetics on Madness and civilization, departing from the discussion about image, the visual and visible on Foucault's work, as well as the relations with between madness and art and the aesthetic dimensions associated with unreason as cultural concept. The dissertation discussed the role of art and aesthetics in the philosophical project undertaken by Foucault in Madness and civilization, as well as his later self-criticism and reinterpretation of this book and his own work